A Fetus with Imperforate Anus Developing Pulmonary Hypoplasia Triggered by Transient Urethral Obstruction - Masatake Toshimitsu; Takayuki Iriyama; Seisuke Sayama; Kan Suzuki; Satsuki Kakiuchi; Mari Ichinose; Takahiro Seyama; Kenbun Sone; Keiichi Kumasawa; Takeshi Nagamatsu; Tomoyuki Fujii; Yutaka Osuga (Case Reports in Obstetrics and Gynecology)
Pulmonary hypoplasia is a rare entity in a fetus with imperforate anus. The fetus was diagnosed with high-type imperforate anus with rectourethral fistula based on the dilated fetal bowel and the presence of bowel calcification at 19 weeks of gestation. As gestation advanced, fetal ultrasonography demonstrated development of pulmonary hypoplasia, progressive bowel dilation, and persistent oligohydramnios from 28 weeks of gestation despite a fluid-filled bladder without hydroureter or hydronephrosis. To prevent further worsening of pulmonary hypoplasia caused by thoracic compression due to bowel dilation and oligohydramnios, a male neonate was delivered by cesarean section at 32 weeks of gestation. The neonate showed respiratory failure requiring full respiratory support. Although a catheter did not pass through the urethra into the bladder at birth, cystourethrography revealed the patency of fistula and stenosed lower urinary tract. Prenatal and postnatal findings strongly suggested that the meconium in the colon might have passed into the urethra in the penis, resulting in the physical blockage of urine outflow to the amniotic space which leads urine flow from the bladder to the colon through the fistula, which resulted in subsequent oligohydramnios and bowel dilation. To the best of our knowledge, this is the first case report of a fetus with imperforate anus developing pulmonary hypoplasia possibly due to urethral obstruction.